Structural organization and polypeptide composition of the avian adenovirus core. - Li, P (1984)
CELO virus (fowl adenovirus 1) contained three core polypeptides of molecular weights 20,000, 12,000, and 9,500. The core was similar to that of human adenoviruses, with some evidence of compact subcore domains. Micrococcal nuclease digestion of CELO virus cores produced a smear of DNA fragments of gradually decreasing size, with no nucleosome subunit or repeat pattern. Moreover, when digested cores were analyzed without protease treatment, there was again no evidence of a nucleosome substructure; neither DNA fragments nor core proteins entered a 4% polyacrylamide gel. The organization of the core is thus quite unlike that of chromatin. Restriction endonuclease analysis of the DNA from digested cores showed that the right end was on the outside of the core. We suggest that adenovirus DNA is condensed into the core by cross-linking and neutralization by the core proteins, beginning with the packaging sequence at the center of the core and ending with the right end of the DNA on the outside.